Plant medicine metabolite Yulinzhu treating neurological disorder causing polycystic ovary syndrome: a systematic review and a meta-analysis - Beibei Jiao; Ruilin Chen; Si Chen; Jian Zhang; Peijuan Wang; Huaijun Zhou; Weibo Zhao (Frontiers Media S.A., 2024)
BackgroundPolycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder that affects women of reproductive age, characterized by chronic anovulation, hyperandrogenism, and polycystic ovarian morphology. Emerging evidence indicates that neurological disorders play a significant role in the etiology of PCOS, highlighting the complex interplay between the central nervous system (CNS) and ovarian function. Yulinzhu, a traditional Chinese medicine (TCM) formulation, has been traditionally used to regulate menstrual cycles and improve fertility. This study aims to investigate the efficacy and mechanisms of Yulinzhu in treating PCOS induced by neurological disorders.MethodsAn extensive literature search was performed across electronic databases such as PubMed, EMBASE, Cochrane Library, and China National Knowledge Infrastructure (CNKI), covering publications up to 1 June 2024. The review included randomized controlled trials (RCTs) that compared Yulin Zhu with placebo, standard care, or other active treatments in patients with PCOS. Two reviewers independently carried out data extraction and quality assessment. Meta-analyses were conducted using both fixed and random-effects models, with heterogeneity evaluated using the I2 statistic.ResultsWe screened 891 records and included 6 studi es in the meta-analysis. The meta-analysis revealed that Yulinzhu about effective rate [RR = 1.19, 95% CI (1.10, 1.29), p < 0.0001], pregnancy rate [RR = 2.80, 95% CI (1.65, 4.76), p < 0.0001] and ovulation rate [RR = 1.33, 95% CI (1.10, 1.62), p = 0.04]. Meta-analysis shows the results of follicle estrogen [WMD = 0.69, 95% CI (−0.39, 1.78), p = 0.21], luteinizing hormone [WMD = −2.27, 95% CI (−3.86, −0.67), p = 0.005], testosterone [WMD = −0.44, 95% CI (−0.64, −0.25), p < 0.0001], estradiol [WMD = 16.20, 95% CI (2.74, 29.67), p < 0.0001].ConclusionThis study demonstrates that plant medicine compund Yulinzhu may effectively treats PCOS including hormonal regulation, anti-inflammatory actions, and neuroprotection. We expect further research with larger, well-designed clinical trials to substantiate our conclusions.